PENGEMBANGAN MEDIA PEMBELAJARAN CALISTUNG BERBANTUAN ANDROID UNTUK ANAK USIA DINI - Ina Rosmalita; Indri Astuti; Marmawi R (Jurnal Education and Development, 2022)
The purpose of this study was to develop a calistung learning application for early childhood 5-6 years. The research method used is research and development (R&D). This research model uses the ADDIE development model. The results of the development of learning media in the form of an android application with APK format. Based on the results of material expert validation, it reached an average of 4.45 with the criteria of "Very Good". The results of the assessment from media experts reached an average of 4.54 with the criteria of "Very Good". The results of the assessment from media experts reached an average of 4.66 with the criteria of "Very Good". the results of the practicality test of the teacher's response were obtained an average of 4.53 or 90.5%, and the results of the student response questionnaire in the small group trial were 4.07 or 83.3%. while the results of field trials reached an average percentage value of 91.4% with the criteria of "Very Good". The results of the effectiveness of using android-assisted learning media are 2.95 with very high criteria. So it can be concluded that the Android-based learning media developed is very suitable for use for PAUD IT Cahaya Bunda in Ketapang Regency.